The Effectiveness Using Drill Bit Sharpening Jig during Practical Practices in Politeknik Muadzam Shah - Syirazi, Mohd; SALLEH, M. HELMI; RIFIN, MOHD RIZAL AZMAN (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2022)
In this study, the effectiveness of the sharpen a blunt drill bit using a develop jig was performed. During the practical practise, the students of Mechanical Engineering at Politeknik Muadzam Shah have to sharpen the drill bit for their practical practice session. It is important to sharpen the drill bit at the right angle and it is challenging when the students use their free hands to sharpen the blunt drill bit. The purpose of this study is to determine the effectiveness of the drill bit sharpening device by surveying the participants. Another purpose of this study is to compare the time taken to sharpen the drill with the free hand and with the drill bit sharpening jig. The total sample used in this study was 126 respondents. During this study, respondents were given the task of sharpening the blunt drills using two methods. The first method was to sharpen the blunt drill with the respondents' free hand and the second method was to use the drill sharpening jig developed by the researchers. The result shows that the respondents had problems sharpening blunt drills with their free hand and took an average of three minutes to sharpen these blunt drills. Moreover, the respondents are not sure that the freehand method of sharpening drills is symmetrical and can produce flawless holes. On the other hand, the respondents were assured that the use of this jig will give a good drill point which will produce a flawless hole. The jig can help the respondents to sharpen the drill bit better and the respondents were confident that this jig can produce a symmetrical drill point angle that can produce a flawless hole. The result showed a time saving of 66.6 % when using the drill bit sharpening jig compared to sharpening a blunt drill with the free hand. Overall, the researcher believes that the product created can provide an effective teaching and learning atmosphere during the practical practice